(untitled) (International Journal of Engineering and Computer Science, 2019)
Selection and placement of appropriate personnel for the right job leads to great success in any organization. However, this is one of the most important activities carried out by Human Resource (HR). Minimizing imprecision and subjective value judgment in personnel selection processes were taken into consideration in this research by developing personnel selection and placement framework using the Mamdani- fuzzy model. This research work is aimed at developing Mamdani- fuzzy framework for academic staff selection and placement. A model with three levels has been developed to manage the database, and the necessary conditions required from applicants for selection and placement, and the consideration of individual temperament was paramount. Tools: Java script and HTML (for the front end) PHP and MySQL (for the database storage as back end). Experimental results using fuzzy classification membership function defined by the truth value of a fuzzy propositional function would also be used as part of the analysis and design. When the need arise, MathLab would be employed for some analysis and simulations. A graphical user interface (GUI) would be developed for all the relevant forms in order to effectively interact with the users of the system